2023
DOI: 10.1029/2022ms003432
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Megafire Smoke Plumes in Climate Models: Why a Converged Solution Matters for Physical Interpretations

Abstract: In the last several years, there has been a dramatic increase in large, intense wildfires ("megafires") in various regions of the world that have burned millions of acres of forests, destroyed homes and businesses and resulted in substantial deaths (e.g., Jolly et al., 2015; Wikipedia contributors, 2022). The production of smoke from these fires can be rapidly transported deep into the stratosphere through a combination of pyrocumulonimbus (pyroCb) events and radiation-driven lift, where it can spread globally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…The overall heating rate of the SWIRL is slightly smaller during this 10-day period, ∼3.7 K/day, indicating less smoke-induced heating than from 13 to 23 February. Further simulations with radiative coupling, such as in Guimond et al (2023), are necessary to elucidate cause and effect.…”
Section: Swirl Forecastsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall heating rate of the SWIRL is slightly smaller during this 10-day period, ∼3.7 K/day, indicating less smoke-induced heating than from 13 to 23 February. Further simulations with radiative coupling, such as in Guimond et al (2023), are necessary to elucidate cause and effect.…”
Section: Swirl Forecastsmentioning
confidence: 99%
“…They showed that the aerosol heating was able to form and maintain synoptic-scale stratospheric anticyclones. A high-resolution (∼7 km) nonhydrostatic simulation of the PNE SWIRL was performed by Guimond et al (2023). They examined the vorticity dynamics of the plume and showed that divergence in the updraft dilutes the background absolute vorticity resulting in an anticyclonic vortex.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we expect that the co-injection of a heating tracer and of air, resulting in a plume initially trapped within a low absolute PV anticyclone, plays a key role in preventing the dilution of the plume along its ascent, through the effects of both dynamical isolation in a low PV vortex and radiative relaxation. However, a few previous studies (e.g., Doglioni et al, 2022;Guimond et al, 2023) have reported on simulations of ATPs that did not include an initial PV anomaly. In order to assess the actual impact of this parameter on the evolution of the plume, we performed a simulation including the same initial tracer field as UP-REF but not the initial PV anomaly; that is, 𝜇 i = 𝜇 (simulation UP-NOPV).…”
Section: Isolation Of the Plume From Environmental Air: Impact Of The...mentioning
confidence: 99%
“…Doglioni et al (2022) simulated smoke-charged vortices in the Goddard Earth Observing System Chemistry Climate Model global model by introducing sunlight-absorbing aerosols. Guimond et al (2023) characterised the sensitivity of global simulations of stratospheric wildfire plumes to model resolution. Though both studies considered the instantaneous tendencies induced by the heating, they did not investigate the mechanisms governing the continuous evolution of the plume.…”
Section: Introductionmentioning
confidence: 99%